1990
DOI: 10.1128/jcm.28.9.2059-2063.1990
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of genomic DNAs of different enterococcal isolates using restriction endonucleases with infrequent recognition sites

Abstract: Epidemiologic evaluation of enterococci has been limited by the lack of a simple and effective method for comparing strains. In this study, we have compared chromosomal restriction endonuclease digestion patterns of 27 isolates of Enterococcus faecalis from three different locations by using pulsed-field electrophoresis of large chromosomal fragments (14 to 1,000 kilobases). AU but two isolates generated a clear, evaluable pattern with a single lysis and digestion, and the remaining two were visualized when a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
227
1
10

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(243 citation statements)
references
References 34 publications
5
227
1
10
Order By: Relevance
“…They differ substantially in the intergenic spacer regions. A Sinai site which is conserved in a variety of gram-positive bacteria [7] is found in the 1.8-but not in the 1.6-kb sequence (Fig. 1B).…”
Section: Methodsmentioning
confidence: 99%
“…They differ substantially in the intergenic spacer regions. A Sinai site which is conserved in a variety of gram-positive bacteria [7] is found in the 1.8-but not in the 1.6-kb sequence (Fig. 1B).…”
Section: Methodsmentioning
confidence: 99%
“…Agarose plugs were prepared [8] and digested overnight with 40-80 units of SfiI or NotI (Boehringer) according to the manufacturer's recommendations. The software-assisted ZIFE electrophoresis apparatus (Auto Base, Q-Life System Inc.) was used with ROM cards that optimize DNA fragment separations in the 100-700 kb (card no.…”
Section: Zero Integrated Field Gel Electrophoresis (Zife)mentioning
confidence: 99%
“…Several approaches for identi¢cation below the species level were developed, among others pulsed ¢eld gel electrophoresis (PFGE) of DNA macrorestriction fragments [2]. The ¢rst study involving enterococci demonstrated the usefulness of the procedure for typing strains of Enterococcus faecalis [3]. Also, for Enterococcus faecium it was demonstrated that PFGE provided an e¤cient procedure for mapping genomic polymorphism in an epidemiologically concordant fashion [4].…”
Section: Introductionmentioning
confidence: 99%